Modeling electromagnetic form factors of light and heavy pseudoscalar mesons - El-Bennich, B.; De Melo, J. P.B.C.; Loiseau, B.; Dedonder, J. P.; Frederico, T. (FapUNIFESP (SciELO), 2008)
The electromagnetic form factors of light and heavy pseudoscalar mesons are calculated within two covariant constituent-quark models, viz., a light-front and a dispersion relation approach. We investigate the details and physical origins of the model dependence of various hadronic observables: the weak decay constant, the charge radius and the elastic electromagnetic form factor.
Keywords: Constituent quark model; Covariance; Electromagnetic current; Electromagnetic form factor; Light-front